Gentrification of the countryside in Southern Tuscany: the invention of Chiantishire - Meloni, Pietro (L'Uomo Società tradizione sviluppo, 2022)
In this article I discuss the production of gentrification of the countryside in Southern Tuscany. The focus is on neorural elitism in Chianti, a geographical area between Florence and Siena renown for wine production. I discuss the data resulting from my ethnographic research on the life and work of two international artists who live in Chianti; their life allows us to understand how gentrification has transformed many rural areas in Central Italy, colonizing the global imaginary on this territory. Gentrification turns the Italian countryside in a hyper-place inhabited by a neoruralist elite. The “invention” of Chianti, transformed in Chiantishire, allows us to understand the changes of contemporary rural world within the global flows that forge the cultural imaginary of “gentle” and “savage” countryside, opposed to the hustle and bustle of contemporary urban life.